The Effectiveness Of Poetic Language According To Ibn Matrouh Between Tradition And Innovation (Journal of the College of Basic Education, 2024)
Ibn Matruh is considered one of the well-known poets of Egypt (d. 649 AH). He gained the admiration of ancient and modern critics because his poetry represented an expression of the reality of the life of Egyptian youth at that time. Ibn Matrouh touched on the poetic language, which is one of the most important elements of poetry. It is the means by which the poet expresses his thoughts, feelings, and artistic visions. Ibn Matruh’s poetry was distinguished by the effectiveness of his poetic language, as he was able to combine tradition and innovation in the use of poetic language. This research studies the effectiveness of this poetic language according to Ibn Matruh between imitation of the ancient and modern renewal.